Assessment of the anatomical knowledge in undergraduate Nursing collage students - merza, alaa (Iraqi National Journal of Nursing Specialties, 2005)
Abstract Objective: The aim of this study is to evaluate the level of the anatomical knowledge of undergraduate students in Nursing collage/Baghdad university.Methodology:The sample was collected by symmetrical probability. Research sample includes (197)students represent four classes which is distributed as following: fifty students represent first class, fifty students represent the second class, forty nine students represent the third class,&fourty eight students represent the fourth class. Results:The study concludes that the anatomical knowledge level for collage students is intermediate .The main level of anatomical knowledge for each class is that as following; medium of intermediate level for the first & the second classes, between the intermediate& good level for the third class,& the highest degree of the passing level for the fourth class. The statistical analysis appears that there are significant differences between male &female in the first, second &third classes while there is no significant difference in the fourth class,& also there are significant differences among the four classes. Recommendation: the semester hours should be increased & the curriculum should be changed to become annular rather than one semester. Key words: (anatomy, knowledge, students, nurse, assessment)